Lawsuit Against The Issuance Of Property Rights Certificates That Are Suspected Of Being Misappropriated (Study Of The Bandung High Court Decision Number 444/Pdt/2024/Pt Bdg) - Riska Nadia Galuh Larasa; Mella Ismelina Farma Rahayu (Jurnal Impresi Indonesia, 2025)
Land disputes in Indonesia often arise from conflicting claims over property certificates, exacerbated by informal proofs like Leter C. This study analyzes the Bandung High Court’s ruling (Decision No. 444/PDT/2024/PT BDG) on an unlawful acts lawsuit challenging the issuance of certificates allegedly misappropriating ancestral land. The research aims to assess the court’s adherence to agrarian laws (UUPA, PP 24/1997) and evaluate the plaintiffs’ failure to prove ownership via certificates. The research used a normative juridical approach, combining statute, conceptual, and case analyses of primary legal materials (court rulings, UUPA) and secondary literature. The court rightly dismissed the lawsuit, affirming certificates as sole valid proof of ownership under Article 19 UUPA. Plaintiffs’ reliance on Leter Ccontravened Supreme Court jurisprudence (No. 023K/PDT/1992), highlighting the need for administrative resolution via BPN before litigation. Strengthens legal certainty in land disputes but underscores systemic inefficiencies in BPN’s mediation. Future research should optimize BPN’s dispute mechanisms and harmonize judicial-administrative coordination.